1997
DOI: 10.1093/oxfordjournals.aje.a009249
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Effects of Ambient Oxidant Exposure on Mortality: A Combined Analysis within the APHEA Project

Abstract: The Air Pollution and Health: a European Approach (APHEA) project is a coordinated study of the short-term effects of air pollution on mortality and hospital admissions using data from 15 European cities, with a wide range of geographic, sociodemographic, climatic, and air quality patterns. The objective of this paper is to summarize the results of the short-term effects of ambient oxidants on daily deaths from all causes (excluding accidents). Within the APHEA project, six cities spanning Central and Western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
106
0
5

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(117 citation statements)
references
References 45 publications
6
106
0
5
Order By: Relevance
“…6 RRs for ozone and NO 2 for total mortality in a number of western European cities were higher in the warm season, although the difference was not statistically significant. 7 For CVD and respiratory mortality in the APHEA study, there was a non-significant tendency toward higher RRs in the warm season, especially for SO 2 . 23 In the present study, the differences for cause-specific mortality were more pronounced.…”
Section: Summer-winter Differencementioning
confidence: 78%
See 1 more Smart Citation
“…6 RRs for ozone and NO 2 for total mortality in a number of western European cities were higher in the warm season, although the difference was not statistically significant. 7 For CVD and respiratory mortality in the APHEA study, there was a non-significant tendency toward higher RRs in the warm season, especially for SO 2 . 23 In the present study, the differences for cause-specific mortality were more pronounced.…”
Section: Summer-winter Differencementioning
confidence: 78%
“…Studies from the United States have reported that daily mortality is especially associated with PM air pollution. 2 Studies from Europe have found associations with gaseous pollutants such as SO 2 6 and NO 2 and O 3 , 7 as well. Relative risks (RR) for PM 10 in the Air Pollution and Health: A European Approach (APHEA) study 6 were generally smaller than those reported for the United States.…”
Section: Introductionmentioning
confidence: 99%
“…In practice however the σ 2 i are not known and the statistic ). This test is frequently used to determine whether the fixed or random effects model should be adopted (for example Touloumi et al 1997;Danesh et al 1998). It has been suggested, however, that the power of this test can be low (Thompson and Pocock 1991;Hardy and Thompson 1998).…”
Section: The Random Effects Methods and Testing For Homogeneitymentioning
confidence: 99%
“…any epidemiological studies have documented adverse short-term effects of different types of air pollution on health outcomes in recent years [1][2][3][4][5]. The pollution indicators used were mainly ambient particles [4,6,7], but gaseous pollutants, such as nitrogen dioxide (NO 2 ), ozone (O 3 ) and carbon monoxide (CO), have also been shown to have adverse effects on mortality and morbidity [3,[8][9][10].…”
mentioning
confidence: 99%